Application of layer-by-layer films in optical and electrical sensors - Alam, Md. Shah; Dutta, Joydeep; Mohammed, Waleed S.; Hornyak, Gabor L.; Asian Development Bank {u2013} Japan Scholarship Program (ADB-JSP) (Pathum Thani : Asian Institute of Technology, 2013)
This thesis demonstrates the theoretical as well as experimental aspect of multilayer thin film based on electrostatic self-assembly of gold and silica nanoparticles from colloidal solutions. A mathematical model is derived to design metallic Bragg grating using plane wave theory and scattering matrix method. Maxwell-Garnett and Bruggeman effective medium approximations are applied in this mathematical model and simulation is conducted by MATLAB to design metallic Bragg grating optical filter with nanoparticles self-assembly. Experimental work is conducted according to the theoretical design through layer by layer (LbL) self-assembly of gold and silica nanoparticles which are done by dip-coating method. A software is made using Microsoft Visual Basic 2008 to operate the dip-coating machine. Silica nanoparticles in different sizes were synthesized and LbL thin film is fabricated on glass substrates. Optical characterization is done to investigate Bragg reflection. LbL thin films are also prepared on FTO and gold coated flexible plastic substrate. Electrical characterization is carried out with different physical conditions such as with different pressures, bending, varying light intensity and temperature. Change in electrical characteristics with different physical conditions make the LbL thin film as a versatile sensor such as a pressure sensor, bending sensor, temperature sensor and solar light intensity sensor.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Nanotechnology
Thesis (M. Eng.) - Asian Institute of Technology, 2013
Keywords: Polyelectrolytes; Thin films, Multilayered; Nanoparticles -- Electric properties